Optimization of collagen-based matrices for skin tissue engineering - Gobardja, Brenda (2017)
In order to fabricate an ideal scaffold to mimic the dermis skin layer, the scaffold must have the main features of the dermis. For the scaffold, several biomaterials mainly natural or synthetic can be used. Natural synthetic biomaterials are more preferable as they are not toxic to the cells. The scaffold in vitro 3D culture system needs to be modified to mimic the real in vivo 3D environment. Several modification methods are present such as the use of mechanical force, crosslinking and macromolecular crowding. In this project, collagen type I is chosen as the biomaterial. Macromolecular crowding is chosen as method to tune the scaffold’s architecture. 2D culture system is also tested via cell viability test to prove that 2D culture system is a less favorable culture system. Polyvinylpyrrolidone (PVP)360 kDa and FVOs of 0%, v/v, 18% v/v, 36% v/v and 54% v/v are shortlisted to be used induce the MMC effect. Human dermal fibroblast cells are added in both 2D and 3D culture system. The presence of fibroblast cells has an effect on the collagen architecture of the 3D culture system. For 2D culture system, average relative fluorescence unit is measured. It is found that as FVO concentration increases, average relative fluorescence unit increases too. For 3D cell culture, characterization of the scaffolds will be done through the use of SEM to capture images and ImageJ to calculate the porosity of the scaffold. SEM images show qualitatively how the porosity level of each FVO concentration and the way human dermal fibroblast cells attached themselves on the scaffold. As for porosity, it was found to decrease along an increase in the FVOs.